2014
DOI: 10.1111/jocs.12368
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Minithoracotomy Approach: Technical Developments Towards Totally Endoscopic Sutureless Aortic Valve Replacement

Abstract: The described approach appears to be safe and feasible with adequate clamp times. Video assistance allows optimal visualization of the aortic root and accurate valve delivery, without conflict between the device, the camera, and the instruments, making this setting an encouraging baseline towards the assessment of the totally endoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Moreover, with the rapid popularization of some specialized centers, MICS has now become the standard method of cardiac surgery [ 14 , 16 ]. Previous studies have reported that MICS is used in almost all types of cardiac surgery, including mitral valve surgery [ 23 ], ASD repair [ 20 , 24 ], VSD repair [ 25 ], AF ablation [ 26 ], CABG [ 22 , 27 ], and myxoma dissection [ 28 ]. Notably, results of randomized clinical trials (RCTs) and meta-analyzes [ 23 ] have clearly proven that MICS is a safe, efficacious, and repeatable alternative to traditional surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with the rapid popularization of some specialized centers, MICS has now become the standard method of cardiac surgery [ 14 , 16 ]. Previous studies have reported that MICS is used in almost all types of cardiac surgery, including mitral valve surgery [ 23 ], ASD repair [ 20 , 24 ], VSD repair [ 25 ], AF ablation [ 26 ], CABG [ 22 , 27 ], and myxoma dissection [ 28 ]. Notably, results of randomized clinical trials (RCTs) and meta-analyzes [ 23 ] have clearly proven that MICS is a safe, efficacious, and repeatable alternative to traditional surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Of 250 potentially relevant articles screened initially, 11 single-arm studies [7][8][9][10][11][12][13][14][15][16][17][18][19] of sutureless/rapid-deployment AVR reporting early mortality and/or overall survival were identified and included (►Table 1). We excluded 18 studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] enrolling <50 patients and 6 studies [38][39][40][41][42][43] (►Table 2) duplicating patients enrolled in other studies. In total, our meta-analysis included data on 2,066 patients undergoing sutureless/rapid-deployment AVR.…”
Section: Resultsmentioning
confidence: 99%
“…Initial insights from this simulation would tend to support the idea of making the incision as superior and lateral as possible. Such an incision would of course preclude direct visualization and favor a video-assisted approach as described by Vola 13 et al Using a 30 o scope may also help avoid the increased difficulty with visualization of the noncoronary aspect of the annulus, which may otherwise be associated with making the chestwall incision too lateral. As reported by Ito et al on their experience in the infra-axillary approach, long shafted instruments would compensate for the longer intrathoracic distances.…”
Section: Discussionmentioning
confidence: 99%